Cultural capital and strategic social marketing orientations. Issue 2 (1st July 2014) - Debra Basil, Dr. Michael Basil, Dr.; Kamin, Tanja; Anker, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The article aims to illuminate this issue by applying the cultural capital theory to the processes of health production and distribution. It questions social marketing's role in addressing cultural resources as barriers to and/or facilitators of behavioural change. Social marketing is often criticized for its limited ability to enhance social goals and for aiding the reproduction of social inequalities. Design/methodology/approach – The theoretical framework of this conceptual paper is based on the French sociologist Pierre Bourdieu's theory of human capital forms. It establishes an association between cultural capital and social marketing in solving social problems. Findings – All social marketing interventions affect cultural resources that people might use in the field of health. The findings endorse the utilization of cultural capital as a strategic analytical tool in social marketing. Practical implications – The article demonstrates how Bourdieu's capital theory can be applied to help social marketers make important strategic decisions. In particular, it argues that using specific notions of embodied cultural capital and objectified cultural capital can inform decisions on adopting a downstream, midstream or upstream approach. Originality/value – A relatively neglected concept in the social marketing field is introduced: cultural capital. It aims to contribute to the theoretical debate with regard to strategic social marketing orientations.